Символическая социальная реальность: методологические подходы и практический опыт изучения - Мартынюк, И.; Соболева, Н. (Социология: теория, методы, маркетинг, 2004)
With the help of the imageandsymbol space category, the authors show a growing role of the subjective factor as dominant in development of modern socium. This is crucial for theoretical and methodological basis formation of sociology in the 21-st century because it determines the basic notions of sociology. The article describes how integral paradigms of sociological postmodernism reveal interrelations of open social structures and active social agents. The researchers prove the necessity of subject subjective relations of different levels and social subjects to be involved into sociological studies. Basing on the data of empirical surveys, the authors present symbolic specific features of the image of Ukraine as Fatherland in the contemporary mass consciousness of its people.